﻿Solubility enhancement of carvedilol by multicomponent crystal approach using glycine and arginine as coformers - Iyan Sopyan; Wuri Ariestika Sari; Sandra Megantara; Taofik Rusdiana (Pensoft Publishers, 2023)
A Carvedilol is a member of BCS class II, it has a low solubility and bioavailability. This work intends to increase the solubility of carvedilol using a multicomponent crystal method. Based on in silico investigations showed that carvedilol-arginine formed one hydrogen bond and carvedilol-glycine formed two hydrogen bonds. Compared to the solubility of pure carvedilol, CVD: GLY multicomponent crystal ratios of 1:1, 1:2, and 2:1 resulted in increases in solubility of 1.9 times, 2.6 times, and 2.5 times respectively. The solubility of the multicomponent crystals in the CVD:ARG however, did not increase. The best dissolution profile was provided by multicomponent crystal CVD: GLY (1:2), with a % dissolution of 86.03% in HCl medium pH 1.45 and 29.5% in phosphate buffer medium pH 6.8. The results of characterization included FTIR, DSC, PXRD, and SEM evaluation of CVD: GLY multicomponent crystal (1:2) indicated the formation of a new solid crystalin phase. CVD: GLY multicomponent crystal (1:2) showing the best solubility and dissolution profile as compared to pure carvedilol.